Faktor-Faktor Yang Mempengaruhi Kejadian Seks Pranikah Pada Remaja Putri Di SMAN 1 Pagai Utara Selatan Kabupaten Kepulauan Mentawai - Romauli ' Hasibuan; Yulia Irvani Dewi; Nurul Huda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract This aimsof this research is to determine the factors that influence of the incidence of premarital sex among female adolescents. Methodology on this research was a descriptive correlative with cross sectional approach. The sample in this research are 118female adolescents in Senior High School 1 South North Pagai Mentawai Islands with stratified sampling technique.Measuring instrumentwas useda questionnaire. The analysis was usedunivariateandbivariateanalysisbyChi-squared test.The results showedthat effect ofpressurefromfriendswith p-value0.025andpovertyinfluence onpremaritalsexwith ap-value<0.05, namely 0.002, while the influenceof pressurefromboyfriends, parental attitudes, shiftingcultural, moralandethicalas well asknowledgehas no effect onpremaritalsex. This studysuggeststo theSenior High School 1 SouthNorthPagaiMentawai islandstogiveeducationandinformationonreproductivehealthandsexualityeducation. so expecta teenagerto knowthe effectsof premarital sexandraise awareness of theinfluence offree associationin public life. Keywords : Incidence of premarital sex, adolescents References: 59 (2004-2013)